THE COOPERATIVE PRINCIPLE ANALYSIS IN FIFTH SEMESTER STUDENTS AT UNDIKMA - Wahyudiantari, Ni Wayan Prami (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This study aimed to analyze the cooperative principle by observing the speech of the fifth semester students of UNDIKMA. Qualitative descriptive method is used in analyzing the data because it will be explained with words, phrases, and sentences. The data will be based on the words of the fifth semester students at UNDIKMA. In collecting data, the researcher used observational and non-participatory methods, and also taking notes. The pragmatic identity method is applied in analyzing the data. The findings show that the four maxims in the cooperative principle are found through the utterances of fifth semester students at UNDIKMA.The researcher found four maxims. The results showed that the maxim of quantity, maxim of relation, maxim of quality and maxim of manner. In conclusion, the most frequent data found in the maxim of quantity and the least data found in the maxim of manner.